Electronic properties of mesostructured metal oxides in dye-sensitized solar cells - Docampo, P; University of Oxford (2012)
Solid-state dye-sensitized solar cells (ssDSCs) offer the possibility of high power conversion efficiencies (PCEs) of over 20%. However, after more than a decade of research, devices still barely reach over 7% PCEs. In this thesis, limitations to device performance are studied in detail, and solutions for future advancement are put forward. In the first part of the thesis, factors limiting charge generation are explored by studying the crystallization environment of mesoporous TiO2 self-assembled through block copolymers. It was found that the density and distribution of sub band gap states are a function of the synthesis conditions and critically affect the performance characteristics of the self-assembled titania used in ssDSCs. As a result, the self-assembled mesoporous oxide system presented in this thesis outperforms for the first time the conventional nanoparticle based electrodes fabricated and tested under the same conditions, with demonstrated PCEs of over 5%. In chapters 6, 7, and 8, the factors limiting the diffusion length and hence, the thickness of the fabricated devices, are carefully examined. Previous literature points towards insufficient pore-filling of the hole transporting material (HTM) as the main limiting factor. In chapter 6, a pore-filling study is shown where a new technique to evaluate the pore-filling fraction of the HTM in the conventional mesoporous metal oxide electrode is also presented and conclude that sufficient pore-filling of thick films can easily be achieved. Another usual strategy to extend the electron lifetime in the devices and thus, the charge diffusion length, involving thin film coatings of insulating metal oxides is examined in chapter 7, with satisfactory results for SnO2-based ssDSCs. The diffusion length can also be extended if the factors limiting the diffusion of charges through the device are identified and removed, as presented in chapter 8. Finally, a study on the stability of the ssDSC is presented in chapter 9. The developments achieved enable long term stability to be effectively targeted, and represent a key milestone towards commercial realization of ssDSCs.